A new tetrapod from Romer's Gap reveals an early adaptation for walking. (March 2017) - Smithson, Timothy R.; Clack, Jennifer A.
ABSTRACT: A new early tetrapod, Mesanerpeton woodi gen. et sp. nov., collected by Stan Wood from the Ballagan Formation, Tournaisian CM palynozone, at Willie's Hole, Scottish Borders, is described. It includes vertebrae like those of Crassigyrinus, with poorly developed neural arches, a well ossified ulna with a large olecranon, and a humerus that is structurally intermediate between the pleisiomorphic condition of Devonian taxa and that of all later forms. A comparative analysis of this new material and other tetrapodomorph humeri revealed how an increase in humeral torsion transformed the course of the brachial artery and median nerve through the bone, from an entirely ventral path to one in which the blood vessel and nerve passed through the entepicondyle from the dorsal to the ventral surface. Increasing humeral torsion is suggested to improve walking in early tetrapods by potentially contributing to an increase in stride length, and is one of a number of changes to limb morphology during the Early Carboniferous that led to the development of terrestrial locomotion.